Respuesta :

Answer:

[tex]\Large \boxed{x=-2 \ \mathrm{and} \ x=3}[/tex]

Step-by-step explanation:

The quadratic expression is given.

[tex]2x^2-2x-12=0[/tex]

Factor the left side of the equation.

[tex]2(x+2)(x-3)=0[/tex]

Set the factors equal to 0.

[tex]x+2=0[/tex]

 [tex]x=-2[/tex]

[tex]x-3=0[/tex]

 [tex]x=3[/tex]

The two solutions work in the original equation. The solutions make the equation true.

The quadratic expression:

[tex]2 {x}^{2} - 2x - 12[/tex]

★ By split middle term,we get

[tex]2 {x}^{2} - 6x + 4x - 12[/tex]

[tex]2x(x - 3) + 4( x - 3)[/tex]

[tex](2x + 4) (x - 3)[/tex]

[tex]2x + 4 = 0 \: \: and \: \: x - 3 = 0[/tex]

[tex]2 x = - 4 \: \: and \: \: x = 3[/tex]

[tex]x = - 2 \: \: and \: \: x = 3[/tex]

Therefore , the two solution of given quadratic equations is -2 and 3.

ACCESS MORE